Perception of male college students of Delhi University regarding the use of mobile health technology as a health promotion tool in India - Krishnan, Gokul Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: Mobile health (mHealth) is a term used for the practice of medicine and public health supported by mobile devices. The mHealth field has emerged as a sub-segment of the eHealth which is the use of information and communication technology for health services. Majority of students own mobile phones and spend several hours per day on mobile phones plus there was an increasing consumer demand for mHealth in India. This ubiquitous presence of mobile phones makes it easier to use them as a health promotion tool. Methods: A cross sectional study was conducted between November 2013 and August 2014 among 274 male college students of Delhi University who were the participants in a randomized intervention trial evaluating the use of mobile text messaging in reducing the lifestyle risk factors and asked about their opinion regarding the mobile health approach. Results: Most of the respondents were aged 17 to 22 years (72%), pursuing science stream of education (68%), with fewer hostellers (36%) than day scholars (64%). Majority of the study participants (>90%) were satisfied with the mobile health messaging approach and most of the students (96%) felt mHealth technology could be a useful health promotion tool in India. Conclusions: The current study shows that majority of the study participants were satisfied in receiving health promotional text messages as a part of mobile health approach and felt that this mHealth technology could be a useful health promotion tool in India. This study shows cost-effective, client-driven and universally available mobile technology can be used as a tool for health promotion.